2013
DOI: 10.3354/dao02626
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic infection by larval helminths in Antarctic fishes: pathological changes and impact on the host body condition index

Abstract: We examined pathological changes and relationship between body condition index (BCI) and parasitic infection in 5 species of fish, including 42 icefish Chionodraco hamatus (Channichtyidae), 2 dragonfish Cygnodraco mawsoni (Bathydraconidae), 30 emerald rock cod Trematomus bernacchii, 46 striped rock cod T. hansoni and 9 dusty rock cod T. newnesi (Nototheniidae) from the Ross Sea, Antarctica. All parasites were identified by a combination of morphology and mtDNA cytochrome-oxidase-2 sequence (mtDNA cox2) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 27 publications
1
43
2
Order By: Relevance
“…Fibrosis lesions associated with small necrosis areas have been reported by SANTORO et al (2013) in antarctic fishes and in this same study it was reported different degrees of chronic inflammation in liver tissue caused by larval forms of Contracaecum osculatum and Diphyllobothriidae, which corroborates the present study. This fact may explain the apparent tuviras resistance that even with intense parasitism by nematodes, with the presence of several endocistos in the liver, can maintain stable health.…”
Section: Discussionsupporting
confidence: 92%
“…Fibrosis lesions associated with small necrosis areas have been reported by SANTORO et al (2013) in antarctic fishes and in this same study it was reported different degrees of chronic inflammation in liver tissue caused by larval forms of Contracaecum osculatum and Diphyllobothriidae, which corroborates the present study. This fact may explain the apparent tuviras resistance that even with intense parasitism by nematodes, with the presence of several endocistos in the liver, can maintain stable health.…”
Section: Discussionsupporting
confidence: 92%
“…Our results contrast with the viewpoint of most conservationists and livestock managers that helminth infections have pernicious effects on fish hosts [8,26]. However, their effects depend on many factors including parasite load [26,49], and our results for the trematode Apatemon sp.…”
Section: Discussioncontrasting
confidence: 99%
“…Parasites are usually assumed to be deleterious for their hosts [26,27], and have typically been linked to hosts with poor body condition (e.g. [27,28]).…”
Section: Introductionmentioning
confidence: 99%
“…Nematode parasites harm their host in different ways, such as causing mechanical injury [35, 36], atrophy of tissues, impairment of host fecundity [37], and pathogenecity of liver [9, 13, 17]. Parasitic helminths in natural habitats can drastically reduce their host fitness, and accordingly the hosts have evolved powerful counter-measures to control infection [38].…”
Section: Discussionmentioning
confidence: 99%